Evaluation of the frequency of left renal vein variations in computed tomography and its relationship with cancer development - (:unkn) unknown (VIA MEDICA, 2020)
Background: Left renal vein (LRV) variations occur in 0.8-10.2% of the population. The most common LRV variations are retroaortic left renal vein (RLRV) and circumaortic left renal vein (CLRV). The purpose of this study is to determine the frequency of LRV variations in a large series on computed tomography (CT) and to investigate the association between LRV and malignancy development. Materials and methods: Between January 2015 and January 2017, an abdominal CT examination of 12,341 (5505 female, 6836 male) patients was evaluated retrospectively in this study. Patients' clinical and demographic data were recorded using the Hospital Information System. Results: Left renal vein variations were detected in 314 (2.54%) of the 12,341 patients within the study. Of the 314 cases found to have LRV variations, 227 (1.84%) had RLRV, and 87 (0.70%) had CLRV. There was no statistical difference in total LRV variations (p = 0.083) and CLRV variation (p = 0.96) groups in terms of gender. However, the RLRV variation was found to be 1.32 times higher in males than in females (p = 0.039). Of the 314 patients with LRV variations, 73 (23.2%) had any sort of concomitant malignancy. Conclusions: A high incidence of malignancy was detected in patients with LRV variations. Of the LRV variations, RLRV variation is more common than CLRV variation. The presence of total LRV variations and CLRV variations is not associated with gender; whereas the presence of RLRV variation is more common in males.
Keywords: renal vein; variation; abnormality; malignancy; computed tomography; circumaortic; retroaortic; INFERIOR VENA-CAVA; CONGENITAL-ANOMALIES; PREVALENCE